Особливості взаємовпливу правосвідомості та вимог до правового статусу суб’єктів доказування в цивільному процесі - Садикова, Яна Михайлівна; Садикова, Я. М.; Sadykova, Yana (ВД "Гельветика", 2020)
У статті зроблено спробу в загальному вигляді висвітлити взаємовплив презюмованого рівня правосвідомості конкретного учасника процесуального доказування цивільного процесу з процесуальним статусом цього суб’єкта. Так, законодавство виходить з презумпції високого рівня правосвідомості осіб, якщо кваліфікаційною вимогою до здійснення ними своєї професійної діяльності є наявність вищої юридичної освіти. А це своєю чергою проявляється в правому статуті через ширше коло обов’язків, більш високі вимоги до виконання такими особами цих обов’язків і, відповідно, встановлення більш суворих санкцій за невиконання або неналежне їх виконання тощо.

The article attempts to generalize the interplay of the presumed level of legal consciousness of a particular participant in the process of proving a civil process with the procedural status of this subject. Taking into account the fact that any procedural activity can be represented in the form of successive specific social ties, the most visible specificity of procedural evidence can be traced through the prism of its subjective composition. It is impossible to characterize the content of the procedural legal relationship and its nature without connection with specific entities. Given this, the objective of the study is to identify the specifics of the evidence-based activities of each of the subjects of the civil process. Legislation proceeds from the presumption of a high level of legal consciousness of persons if the qualification requirement for their professional activity is the presence of a higher legal education. And this, in turn, is manifested in the legal status through a wider range of duties and higher requirements for such persons to fulfill these duties and, accordingly, the establishment of more stringent sanctions for non-fulfillment or improper fulfillment of them and the like. The regulatory function of legal consciousness is determined by the property of consciousness not only to reflect reality, but also to direct human activities to transform the surrounding world. The application of knowledge by the court or other entities of the process that go beyond the framework established by the procedural law is nothing more than a manifestation of legal awareness in legal proceedings. Each participant in the process fulfills its procedural role and at the same time displays its legal consciousness. In proving it is possible to identify the participant of knowledge, the participant of explanations, the participant of interpretation, and the like. Depending on the purpose of participation of a certain subject in the process of judicial proof, the legislation defines the legal status of such a subject.
Садикова, Я. М. Особливості взаємовпливу правосвідомості та вимог до правового статусу суб’єктів доказування в цивільному процесі / Я. М. Садикова // Часопис цивілістики : наук.-практ. журн. / редкол.: Є. О. Харитонов (голов. ред.), О. І. Харитонова (заст. голов. ред.), К. Г. Некіт (відп. секр.), чл. редкол.: С. В. Ківалов, В. В. Завальнюк [та ін.]. – Одеса : Гельветика, 2020. – Вип. 36. – С. 82-88.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; доказування; суб’єкт доказування; правосвідомість; правовий статус; цивільний процес; proof; subject of proof; legal consciousness; legal status; civil process